Effect of Gelatin Concentration on Physicochemical and Organoleptic Characteristics of Chinese Lemon Jelly Candy (Citrus microcarpa) - Nina Timisela; Rachel Breemer; Vita N Lawalata (Jurnal Agrosilvopasture-Tech, 2023)
Jelly candy is candy that is processed using the addition of hydrocolloids such as starch, agar, carrageenan, pectin, gum gelatin and others with the aim of producing a chewy texture to the product (SNI 547.2-2008). The purpose of this study was to determine the proper concentration of gelatin to get good Chinese lemon jelly candy. This study used RAL with one factor, namely the concentration of gelatin with 3 levels of concentration treatment as follows: P1 = 20%, P2 = 25% and P3 = 30%. The results of the jelly candy study with the treatment of 25% gelatin concentration were the best treatment based on chemical and physical characteristics including 36.33% water content, 0.24% ash content, 57.15% total sugar. pH 5.20, vitamin C 0.014%, color (b) 4.57, firmness 45.18 Nnm. Meanwhile, based on the organopletic test, the treatment with a concentration of 25% gelatin was the best treatment including color, taste, elasticity, and overall.